Pathophysiological and clinical point of view on Kawasaki disease and MIS-C - Vaňková, Lenka; Bufka, Jiří; Křížková, Věra (Pediatrics & neonatology, 2023)
This article compares two important pathophysiological states, Kawasaki disease, and multisystem inflammatory syndrome, in children associated with COVID-19 (MIS-C). Both occur predominantly in children, have a temporal association with an infectious agent, and are associated with immune-system alteration and systemic inflammation under certain circumstances. The two share common pathophysiology, including enhancement of interleukin-1 neutrophils, activation of the inflammasome, pyroptosis, or NETosis. Moreover, the clinical presentation of the diseases overlaps. However, they are indeed two separate diseases, proven by the differences in the epidemiological and etiological aspects and the pathophysiological processes involved in the development and frequency of some clinical signs. This article highlights potentially exciting areas that have not yet been studied in detail, which could help better understand the development of these diseases.
Keywords: COVID-19; lidé; zánět; dítě; Child; Kawasakiho syndrom; Humans; Systemic Inflammatory Response Syndrome; syndrom systémové zánětlivé reakce; Inflammation; Mucocutaneous Lymph Node Syndrome